The Michael Chekhov handbook : for the actor - Petit, Lenard (Routledge, 2020)
"The Michael Chekhov Handbook is a practical guide to Chekhov's supportive techniques for actors, fully updated with new exercises that examine the relationship between the sensations of the physical body and the imagination."--